Altitude and Attitude Control of a Trirotor UAV - Ismail, Mohd Khairuddin; Anwar, P. P. Abdul Majeed; Ann, Lim; Mohd Azraai, M. Razman; Abdul Aziz, Jaafar (Trans Tech Publications, Switzerland, 2014)
This paper outlines the dynamic modelling as well as the attitude and altitude control of a rotary based unmanned aerial vehicle (UAV). A multirotor vertical take-off and landing (VTOL) UAVs, namely Trirotor aircraft is investigated. In essence the the trirotor model consists of three DC motors equipped with three fixed pitch angle rotors without the aid of a swashplate. The mathematical modelling of this multirotor is governed by the Newton-Euler formulation. A classical control algorithm viz. heuristic (Proportional-Integral-Derivative) PID tuning was adopted in the attitude and altitude control of this particular multirotor configuration. It was established from the Simulink simulations that, a PD controller was suffice to control the attitude whilst PID was apt for controlling the altitude of this form of multirotor.